Measuring Contingency Factors in the Application of Knowledge Management in the XYZ College Session Management System Process - Aulia Faradilla Jasmine; Ida Nurlela; Jenyta Primaranti; Satria Valerian Shari; Riya Widayanti (Gayaku Publisher, 2024)
The phenomenon of knowledge management can be seen as a desire to restore the essence of